SYSTEMATIC LITERATURE REVIEW: TRANSFORMATION OF ISLAMIC EDUCATION ADMINISTRATION IN THE ERA OF MADRASAH DIGITALIZATION - Darimus Darimus (Education Studies and Teaching Journal (EDUTECH), 2026)
The digital disruption era compels madrasahs to undergo fundamental transformations in their managerial systems to maintain relevance and enhance competitiveness. This study aims to map global literature regarding the transformation of Islamic education administration with a focus on three main pillars: leadership, governance, and human capital. Utilizing a Systematic Literature Review (SLR) method with the PRISMA protocol, this study analyzes articles from the Scopus databases published between 2014 and 2024. Research findings indicate that digital transformation triggers a shift in the role of madrasah heads toward transformational leadership that orchestrates technology and organizational culture. In the governance pillar, a transition toward Governance 4.0 occurs through the integration of management information systems that improve transparency and accountability. Furthermore, human capital readiness is found to be a critical determinant requiring continuous professional development. Theoretically, this research synthesizes Islamic values, specifically the principles of Amanah (accountability) and Itqan (professionalism), as ethical foundations in data governance and digital administration. These results provide a framework for stakeholders to optimize the digital madrasah ecosystem without compromising the identity of Islamic values.